2014
DOI: 10.1177/0022487114560908
|View full text |Cite
|
Sign up to set email alerts
|

Democratizing Teacher Education

Abstract: In this article, the authors argue that teacher education needs to make a fundamental shift in whose knowledge and expertise counts in the education of new teachers. Using tools afforded by cultural historical activity theory (CHAT) and deliberative democracy theory, they argue that by recasting who is considered an expert, and rethinking how teacher candidates and university faculty cross institutional boundaries to collaborate with communities and schools, teacher education programs can better interrogate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
0
30

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(204 citation statements)
references
References 50 publications
4
170
0
30
Order By: Relevance
“…Para formar um professor não bastam as universidades e as escolas. É preciso também a presença da sociedade e das comunidades locais (ZEICHNER; PAYNE; BRAYKO, 2015). A profissão docente sempre se caracterizou por uma forte intervenção pública, ainda mais necessária em "tempos de desumanização" (ANDREWS; BARTELL; RICHMOND, 2016).…”
Section: Um Novo Lugar Institucional Para a Formação De Professoresunclassified
See 1 more Smart Citation
“…Para formar um professor não bastam as universidades e as escolas. É preciso também a presença da sociedade e das comunidades locais (ZEICHNER; PAYNE; BRAYKO, 2015). A profissão docente sempre se caracterizou por uma forte intervenção pública, ainda mais necessária em "tempos de desumanização" (ANDREWS; BARTELL; RICHMOND, 2016).…”
Section: Um Novo Lugar Institucional Para a Formação De Professoresunclassified
“…Neste lugar produz-se uma terceira realidade, com novos sentidos. Não se trata, apenas, de levar a universidade às escolas ou de trazer as escolas até a universidade, mas sim de construir um novo lugar, em conjunto, em colaboração, valorizando os conhecimentos e as experiências de todos (ZEICHNER; PAYNE; BRAYKO, 2015). Este ponto é particularmente importante, pois obriga a dar igual dignidade a todos os intervenientes no processo de formação.…”
Section: Um Novo Lugar Institucional Para a Formação De Professoresunclassified
“…Democratic professionalism requires professional networks and professionals who collaborate beyond their workspace, including with their students, parents, members of the community and health professionals. This approach to professionalism has also been labelled extended professionalism (Hoyle, 1982) and the community teacher approach (Zeichner, Payne and Brayko, 2015).…”
Section: A Framework Of Different Approaches To Professionalismmentioning
confidence: 99%
“…Notable work has been done by Morva McDonald, Ken Zeichner, and their colleagues at the University of Washington, where they have designed and examined a set of increasingly community-centered teacher preparation efforts at both the elementary and secondary levels. (This work is described in more detail in Zeichner, Payne, and Brayko (2014). McDonald, Bowman, and Brayko (2013), for example, have shown that as a result of community-based placements, teacher candidates are able to recognize and purposefully develop practices that significantly enhance their relationships with students.…”
Section: Building Upon Current Effortsmentioning
confidence: 99%